CONSTRUCTION AND VALIDITY OF THE ADAPTATION LEVEL SCALE OF THE PERSON WITH OSTOMY (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To construct and validate the content of the scale for verifying the level of adaptation of the person with ostomy. Method: Methodological study involving two stages: construction based on two integrative literature reviews and qualitative study with people with stomas; and content validity with judges of the following criteria: behavioral, objectivity, relevance, clarity, simplicity, variety in relation to language; carrying out the pilot test with the target group; lexical and grammatical correction and resubmission to the content validity index. Results: in the first stage, thirteen items received suggestions for improvement, three items were unified by similarity and one was excluded. After the adjustments, a consensus was reached among the judges regarding the representativeness of the items and permanence in the modes based on the evaluated criteria. The target population judged the items as easy to understand, followed by grammatical and lexical correction. Conclusion: The scale presented evidence of content validity demonstrating consensus between the judges and the population.